2018
DOI: 10.5152/turkjsurg.2017.3730
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis of rectosigmoid colon mimicking gastrointestinal stromal tumor

Abstract: Endometriosis is defined as the growth of functional endometriotic gland and stroma outside uterine cavity. Although it is common in women of reproductive age, extragenital endometriosis is considerably rare. Due to the frequent localization at the rectosigmoid junction in the gastrointestinal system, endometriosis may manifest with abdominal pain, constipation, and rectal bleeding. Gastrointestinal stromal tumor is the most common mesenchymal tumor of the gastrointestinal system and develops from muscularis p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…Because ERAS is an operation process gradually expanded on its core concepts (such as preoperative education and evaluation, avoiding intestinal preparation, preventing thrombosis and infection, perioperative anesthesia management, preventing intraoperative hypothermia, early pulling out of the gastric tube, early eating after operation, etc. ), it can be observed that there are differences in operation processes between different diagnosis and treatment centers, but similar results can be achieved in the end [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 97%
“…Because ERAS is an operation process gradually expanded on its core concepts (such as preoperative education and evaluation, avoiding intestinal preparation, preventing thrombosis and infection, perioperative anesthesia management, preventing intraoperative hypothermia, early pulling out of the gastric tube, early eating after operation, etc. ), it can be observed that there are differences in operation processes between different diagnosis and treatment centers, but similar results can be achieved in the end [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 97%
“…We would like to congratulate the authors for publishing such an informative and interesting article (1). We totally agree with the authors to proceed with various modalities and evaluation in this patient who presented with pelvic pain and abdominal bloatedness as it is not easy to diagnose rectosigmoid endometriosis solely by history and physical examination (2,3).…”
Section: Dear Editormentioning
confidence: 87%